Aerospace series. Heat resisting alloy X6NiCrTiMoV26-15 (1.4980). Softened and cold worked. Wires for forged fasteners. D ≤ 15 mm. 900 MPa ≤ Rm ≤ 1 100 MPa. (18th March 2021) - British Standards Institution,
No abstract available